The Meaning of Communication Politeness Viewed from the Qur'an’s Perspective - Zahid, Moh. Zahid (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2022)
This study examines how to build politeness in communication from the perspective of the Qur'an. The research problems raised in this study revolve around two research questions, what is politeness in communication? How to do polite communication from the perspective of the Qur'an? Methodologically, this is a literature study that uses qualitative research. The data used in this study consisted of two, primary and secondary data. Primary data contains a religious textual basis sourced from the Qur'an, while secondary data is in the form of information or literature explanation obtained from various literature sources, especially library sources that are related to the focus of the problem in this study. Based on the research of data analysis, the study found two important findings; First, politeness in communication is a social relationship based on kindness and subtlety in speech, full of calm and gentleness, avoiding all forms of speech or speech that are bad, rude, and loud. Second, in the Qur'an, the recommendation to humans to instill the values of politeness in communication can be found in many verses such as the recommendation to speak with noble words (qoulan karima), pleasant words (qoulan Maysura), good words (qoulan ma'rufa), gentle words (qoulan Layyina), honest words (qoulan sadid), and a number of other words that have a similar meaning to it.